PENINGKATAN DAYA SAING UMKM MELALUI PENGEMBANGAN KUALITAS SUMBER DAYA MANUSIA - Riana Dewi Kartika; Ni Made Wulan Sari Sanjaya (Universitas Panji Sakti, 2026)
This study aims to analyze the influence of developing HR quality on increasing MSME competitiveness. The method used was a qualitative approach, with data collection techniques through interviews, observations, and documentation studies of MSMEs. The results indicated that HR quality, including knowledge, skills, managerial abilities, and technology utilization, significantly influences MSME competitiveness. Businesses with better HR are able to produce higher-quality products, innovate, and utilize digital technology in marketing, thereby expanding market reach. However, limitations remain in financial management and digital literacy. Therefore, efforts are needed to improve HR quality through training, mentoring, and technology utilization so that MSMEs can compete more effectively in the digital era.